What Has Bariatric Surgery Taught Us About the Role of the Upper Gastrointestinal Tract in the Regulation of Postprandial Glucose Metabolism? - Ma, Jing; Vella, Adrian (Frontiers in Endocrinology, 2018)
The interaction between the upper gastrointestinal tract and the endocrine system is important in the regulation of metabolism and of weight (Figure1). The gastrointestinal tract has a heterogeneous cellular content and comprises a variety of cells that elaborate paracrine and endocrine mediators that collectively form the entero-endocrine system. The advent of therapy that utilizes these pathways as well as the association of bariatric surgery with diabetes remission has (re-)kindled interest in the role of the gastrointestinal tract in glucose homeostasis. In this review we will use the changes wrought by bariatric surgery to provide insights into the various gut-pancreas interactions that maintain weight, regulate satiety and limit glucose excursions after meal ingestion.